The Effect of 6 Principles of Household Food Sanitation Hygiene on The Incidence of Diarrhea in Toddlers In The Working Area of The Krayan Public Health Center, Long Ikis District, Paser Regency In 2022 - Ilham Rahmatullah (Sean Institute, 2023)
In the working area of the Krayan Health Center, 6 principles of household food sanitation hygiene greatly influence the incidence of diarrhoea in toddlers. The purpose of this study was to determine the effect of 6 principles of household food sanitation hygiene on the occurrence of diarrhoea in toddlers in the working area of the Krayan Health Center, Long Ikis District, Paser Regency. The type of research used in this research is quantitative with a cross-sectional approach. The informant selection technique is total sampling. The results showed that the 6 principles of household food sanitation hygiene with the incidence of diarrhoea in the Krayan Health Center area showed that there was an influence on the incidence of diarrhoea in toddlers. It was concluded that 6 principles of food sanitation hygiene have an effect on the incidence of diarrhoea in toddlers. It is suggested that the Krayan Community Health Center is expected to be able to provide counselling to residents about how to apply the 6 principles of food sanitation hygiene in order to provide motivation to residents.